Abordagem CTSA e poluição em livros didáticos de biologia do ensino médio - Biava, Gislayne Rodrigues (2010)
The didactic book, used many times as an important instrument of the basic education, receive lots of criticism, including an inappropriate language and the deflection between the contests of the book and the reality of the student. This study has the objective of analyze the pollution theme in three didactic books of college classes. The method was based in create a contests analysis and to evaluate the scientific contents in the books and if the books are adequate for a contemporary education as the STSA (science, technology, society and ambient) approach emphasize, in a new tendency of the didactic science, the search teaching, that let a citizen able to make up one's mind. The results show that these three didactic books bring up some mistakes about the scientific content and can't totally contribute to help in the formation of aware citizen to take decisions, but they present some features that indicate they are in the right way for this new perspective of teaching.